The Effect of Government Teacher Certification on Teaching Performance: Certified vs Uncertified - Limbong , Mesta; Lumbantoruan, Jitu Halomoan (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
The Indonesian government encourages all teachers to be certified in the hope of improving teachers’ performance. The purpose of this study was to explore the effect of teacher certification on teacher performance in the northern Toraja region. Utilizing quantitative methods approach, this study randomly sampled 94 students and teachers. The students were subject to a distribution instrument to evaluate the performance of certified and uncertified teachers. To support the quantitative data a short interview was conducted to 10 randomly selected teachers regarding their perception of the relation between certification and teacher performance. The collected data were subjected to validation test, reliability test and simple linear regression test. The results show that there are 33.75% students strongly disagree with the performance of certified teachers who have been certified but there are 65.85% who agree and strongly agree with the performance of teachers who have been certified. While teachers who have not been certified 35.16% strongly disagree and disagree with the performance of teachers who have not been certified and only 53.88% agree and strongly agree. Conclusively, there is an effect of teacher certification on teaching performance although not very significant between certified and uncertified teachers. Some recommendations for the government regarding the current practice of teacher certification are included.